Relationship Age, Type Gender And Sleep Patterns To Incident Hypertension In The Elderly At Posyandu Sari Waluyo - Marfuah, Dewi; Lutfianto, Dodik; Rahmawati, Nisaa (Sean Institute, 2022)
Background Rear : several causative factor _ happening hypertension , among others age , type gender , history family , obesity , less activity physical , smoking , excessive salt consumption , consumption alcohol , stress , depression , support low social and quality _ sleep . Purpose : find out connection age , type gender and pattern Sleep to incident hypertension in the elderly at Posyandu Sari Waluyo. Method : research This performed on 100 samples , with _ use saturated sampling technique . The design used in research This is analytic observational with approach cross sectional with data analysis using Chi Square test . Age data taken use method interviews , quality data Sleep taken use questionnaire , as well pressure blood checked using a sphygmomanometer. Results : results study This show that the sample mean are in category age elderly end (68%), manifold sex female (64%), pattern Sleep bad (64%), and hypertension with category stage I (68%), Relationship between age to incident hypertension in the elderly (p=0.007). Connection type sex to hypertension in the elderly (p=0.434). Connection between quality Sleep to incident hypertension in the elderly (p = 0.266), Conclusion: There is connection between age to incident hypertension in the elderly . No There is connection type gender and pattern Sleep to incident hypertension in the elderly at Posyandu Sari Waluyo.